An example application of the CEN Water quality — Guidance standard for assessing the hydromorphological features of rivers to the River Frome, Dorset, Southern England - Gurnell, Angela M.; Grabowski, Robert C. (UK Centre for Ecology and Hydrology, 2020)
This report documents a comprehensive application of the framework proposed in CEN Standard CEN/ TC 230/ WG 25/ EN14614 to the River Frome, Dorset, Southern England. Therefore, this report needs to be read with reference to that Standard. The framework was first developed in REFORM, a European Union Framework 7 project (Grant Agreement 282656), established to improve the success of hydromorphological restoration. The Standard determines the natural hydromorphological condition of rivers for many applications. It is appropriate for long-term, catchment-scale management, e.g. river basin planning and implementation. It is also able to support assessments for site-scale, project delivery, e.g. flood management schemes, channel maintenance and channel restoration. The hierarchical and multiscale nature of the analysis illustrated in this report provides causative links between catchment processes and local scale hydromorphological conditions; for example, how catchment scale issues influence fine sediment erosion, transfer and deposition. In this way it can facilitate the application of a DPSIR (Drivers, Pressures, State, Impact, Response) model of management intervention, illustrate causes and consequences, and help target sustainable management solutions.